Efficacy and Safety of Programmed Death-Ligand 1 Inhibitor Plus Platinum-Etoposide Chemotherapy in Patients With Extensive-Stage SCLC: A Prospective Observational Study - Kenji Morimoto, MD, PhD; Tadaaki Yamada, MD, PhD; Takayuki Takeda, MD, PhD; Shinsuke Shiotsu, MD; Koji Date, MD; Taishi Harada, MD; Nobuyo Tamiya, MD, PhD; Yusuke Chihara, MD, PhD; Osamu Hiranuma, MD; Takahiro Yamada, MD, PhD; Hibiki Kanda, MD; Takayuki Nakano, PhD; et al. (JTO Clinical and Research Reports, 2022)
Introduction: To date, the efficacy and safety of programmed death-ligand 1 (PD-L1) inhibitor plus platinum-etoposide chemotherapy for patients with extensive-stage SCLC (ES-SCLC), with real-world evidence, stratified on the basis of age and performance status (PS), have not been fully investigated. The aim of this study was to evaluate the efficacy and safety of PD-L1 inhibitor plus platinum-etoposide chemotherapy in patients with ES-SCLC. Methods: This multicenter prospective study evaluated patients with ES-SCLC who received PD-L1 inhibitor plus platinum-etoposide chemotherapy between September 2019 and October 2021. Results: A total of 45 patients with ES-SCLC received the aforementioned treatment, including 18 elderly (≥75 y old) patients and six patients with a PS of 2. Multivariate analysis indicated that a PS of 2 was a significant independent prognostic factor for progression-free survival and overall survival (p = 0.008 and p = 0.001, respectively). Of patients with PS of 2 at the initial phase, those that achieved PS improvement during treatment had significantly longer progression-free survival and overall survival than those who did not (p = 0.02 and p = 0.02, respectively). The incidence of adverse events accompanied with treatment discontinuation was significantly higher in the elderly patients than in the non-elderly patients (p = 0.03). Conclusions: This real-world prospective study found that PD-L1 inhibitor plus platinum-etoposide chemotherapy had limited efficacy in patients with ES-SCLC with a PS of 2, except for cases with improvement of PS during treatment. Owing to the emergence of adverse events and treatment discontinuation, this treatment should be administered with caution in elderly patients with ES-SCLC.